Structure of the Mangrove Community in the Pangkalan Jambi Village, Bukit Batu District, Bengkalis - Asraf Octaviari; Syafruddin Nasution; Feliatra Feliatra (Jurnal Perikanan dan Kelautan, 2026)
ngroves are coastal ecosystems that play a very important ecological and economic role. This study aims to analyze mangrove species, density, and importance index. The method used was a survey method with the determination of research stations using purposive sampling, where the research location was divided into 3 stations based on criteria, namely station 1 mangrove forest located in Damai Village with relatively good mangrove conditions, station 2 mangrove forest located in Rukun Village which is a mangrove ecotourism area, and Station 3, a mangrove forest located in Murni Village, which is adjacent to a residential area. The results of water quality parameter measurements in Pangkalan Jambi Village showed salinity values of 19-22, pH values of 5.4-6.5, and temperatures of 29-30 ℃. Based on the study, five mangrove species were found in the mangrove forest area of Pangkalan Jambi Village: Rhizophora apiculata, Xylocarpus granatum, Nypa fruticans, Avicennia marina, and Talipariti. tiliaceum. The density in the tree category at station I had the highest density, 1566.66 ind/ha, while the lowest was at station II, 300 ind/ha. In the seedling category, the highest density was found at station I with a density value of 4800 ind/ha, while the lowest density was found at station II with a density value of 3466.67 ind/ha. In the seedling category, the highest density was found at station I with a density value of 7500 ind/ha, while the lowest density was found at station II with a density value of 5000 ind/ha. Based on the average Importance Value Index calculation, the highest INP value was R. apiculata at 249.295%, and the lowest was S. alba at 178.588%.